2022
DOI: 10.1021/acs.jctc.1c01288
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Study of Ligand–Protein Relative Binding Free Energy Calculations: Actionable Predictions from Statistically Robust Protocols

Abstract: The accurate and reliable prediction of protein–ligand binding affinities can play a central role in the drug discovery process as well as in personalized medicine. Of considerable importance during lead optimization are the alchemical free energy methods that furnish an estimation of relative binding free energies (RBFE) of similar molecules. Recent advances in these methods have increased their speed, accuracy, and precision. This is evident from the increasing number of retrospective as well as prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 71 publications
(268 reference statements)
3
49
0
Order By: Relevance
“…Only by large scale ensemble sampling can the nature of statistical distributions of free energies be assessed; we have previously shown that they exhibit non-normal behavior. 8 , 16 , 18 , 19 Binding free energies obtained from independent replica simulations of the same molecular system can vary by a wide range, while their distributions deviates from the Gaussian behavior usually assumed as we have reported. 16 Such properties are important for the proper use of many statistical methods (discussed further in Section 3.5 ).…”
Section: Introductionsupporting
confidence: 45%
See 4 more Smart Citations
“…Only by large scale ensemble sampling can the nature of statistical distributions of free energies be assessed; we have previously shown that they exhibit non-normal behavior. 8 , 16 , 18 , 19 Binding free energies obtained from independent replica simulations of the same molecular system can vary by a wide range, while their distributions deviates from the Gaussian behavior usually assumed as we have reported. 16 Such properties are important for the proper use of many statistical methods (discussed further in Section 3.5 ).…”
Section: Introductionsupporting
confidence: 45%
“… 8 , 16 , 18 , 19 Binding free energies obtained from independent replica simulations of the same molecular system can vary by a wide range, while their distributions deviates from the Gaussian behavior usually assumed as we have reported. 16 Such properties are important for the proper use of many statistical methods (discussed further in Section 3.5 ). ESMACS and TIES are performed using a binding affinity calculator (BAC), 20 which is a computational pipeline to automate the processes of building, running, and marshaling the molecular dynamics simulations, as well as collecting and analyzing data.…”
Section: Introductionsupporting
confidence: 45%
See 3 more Smart Citations